The Effect of Cucumber Fruit (Cucumis Sativus L) on pH Saliva at The Rapha-EL Orphanage Foundation - Molek; Sinta Marito; Mangatas Halomoan Parluhutan Hutagulung (Eureka Herba Indonesia, 2021)
Increasing the pH of saliva will affect oral health. One way to increase the pH of saliva is to chew fruit that is fibrous, crunchy, and contains lots of water. The research objective was to determine the effect of cucumber on salivary pH at the Bina Mandiri Social Orphanage. This type of research is a one-group pretest and posttest group design. The study population was the children at the Rapha-El Orphanage Foundation. The sample size is determined based on the Roscoe formula of 20 people. Methods of data collection by measuring the pH of saliva before and after chewing cucumbers using a digital pH meter. The data that has been collected, is then analyzed by paired t-test. The results showed that there was a difference in the average pH of saliva before and after chewing cucumber (p = 0.001). The conclusion is that there is an effect of chewing cucumber on increasing the pH of saliva in children at the Rapha- El Orphanage Foundation.